National Rates of Nonadherence to Antihypertensive Medications Among Insured Adults With Hypertension, 2015. Issue 6 (December 2019) - Chang, Tiffany E.; Ritchey, Matthew D.; Park, Soyoun; Chang, Anping; Odom, Erika C.; Durthaler, Jeffrey; Jackson, Sandra L.; Loustalot, Fleetwood
Abstract : Despite the importance of antihypertensive medication therapy for blood pressure control, no single data system provides estimates of medication nonadherence rates across age groups and health insurance plans types. Using multiple administrative datasets and national survey data, we determined health insurance plan-specific and overall weighted national rates of nonadherence to antihypertensive medications among insured hypertensive US adults in 2015. We used 2015 prescription claims data from Medicare Part D and 3 IBM MarketScan databases (Commercial, Medicaid, Medicare Supplemental) to calculate medication nonadherence rates among hypertensive adults aged ≥18 years with public or private health insurance using the proportion of days covered algorithm. These findings, in combination with National Health Interview Survey findings, were used to project national weighted estimates of nonadherence. We included 23.8 million hypertensive adults who filled 265.8 million prescriptions for antihypertensive medications. Nonadherence differed by health insurance plan type (highest for Medicaid members, 55.4%; lowest for Medicare Part D members, 25.2%). The overall weighted national nonadherence rate was 31.0%, with greater nonadherence among women versus men, younger versus older adults (aged 18–34 years, 58.1%; aged 65–74 years, 24.4%), fixed-dose combination medication nonusers (31.2%) versus users (29.4%), and by pharmacy outlet type (retail only, 30.7%; any mail order, 19.8%). In 2015, almost one-third (≈16.3 million) of insured US adults with diagnosed hypertension were considered nonadherent to their antihypertensive medication regimen, and considerable disparities were evident. Public health and healthcare professionals can use available evidence-based interventions to address nonadherence and improve blood pressure control. Abstract : Supplemental Digital Content is available in the text.